Legal avenue in Malaysia for recovering unlawful money in business transaction / Nurazlina Abdul Raof and Norazlina Abdul Aziz - Abdul Raof, Nurazlina; Abdul Aziz, Norazlina (2023)
Receiving payment for things or services offered is a prerequisite and customary in business transactions. Unbeknownst to the seller, the payment may come from unlawful money, such as bribery. Such gains are unlawful under Malaysian law and allow the authority to seize the unlawful property/asset/money. However, one pertinent issue is whether the relevant governmental authority can recover the illicit money. When the seller receives payment in good faith as payment consideration, the authority becomes unclear. By utilising the doctrinal approach, this paper examines the application of the relevant civil forfeiture provisions in the Anti-Money Laundering, Anti-Terrorism Financing And Proceeds of Unlawful Activities Act 2001 (Sections) in recovering unlawful money in business transactions. This paper looks at the civil forfeiture laws concerning business transactions, to elucidate the strengths and weaknesses of the Malaysian legal framework. The study unravels the impediments to the effective implementation and enforcement of the said provisions. The research is confined to examining the statute and case laws. Civil forfeiture is unlikely to succeed if a seller accepts payment in good faith, without any awareness that the funds are derived from illegal acts. The study findings may assist relevant parties in comprehending the hindrances and impracticality of the existing legal requirements in retrieving unlawful money in business transactions.